Anti-inflammatory, antioxidant, and antimicrobial evaluation of morin - Sales, Luciana Solera [UNESP]; Hewitt, Benjamin; Muchova, Maria; Brighenti, Fernanda Lourenção [UNESP]; Kuehne, Sarah A; Grant, Melissa M; Milward, Michael R (Elsevier, 2025)
OBJECTIVES: This study aimed to evaluate the anti-inflammatory and antioxidant activity of morin in an epithelial cell culture inflammatory model, as well as its antimicrobial activity against periodontal pathogens. Effects of morin alone or slow-release from a polymer-based formulation were compared. METHODS: An oral epithelial cell line (H400) was pre-conditioned with 0.125 mg/mL morin (free morin or morin in the formulation) for 8 h. The cells were challenged with heat-killed Fusobacterium nucleatum and Porphyromonas gingivalis (MOI 100:1) for 24 h. The production of GM-CSF was measured by enzyme-linked immunosorbent assay (ELISA) and the gene expression levels of IL-8, GM-CSF, IL1B, NF-kB and NLRP3 were evaluated by RT - PCR. Neutrophils were pre-conditioned with 0.01 mg/mL morin and stimulated immediately with heat-killed F. nucleatum or P. gingivalis (MOI 100:1) for 2.5 h and then total reactive-oxygen-species (ROS) levels were determined using enhanced chemiluminescence. F. nucleatum and P. gingivalis as well as a multi-species biofilm (Streptococcus oralis, F. nucleatum and P. gingivalis) were exposed to 1 mg/mL morin for 24 h, planktonic culture and for 7 days, multi-species biofilm. After exposure, the microbial viability (CFU/mL) and biofilm biomass (crystal violet assay) were determined. Live/dead staining and confocal laser scanning microscopy were also performed. Data were submitted to one way ANOVA followed by Tukey's post-hoc test (α=0.05). RESULTS: Morin and the polymer-based formulation containing morin significantly attenuated secretion of GM-CSF, significantly reduced ROS generation and the gene expression levels of the cytokines tested (p < 0.05). Microbial viability and the biofilm biomass significantly reduced (p < 0.05) after treatment with morin and the polymer-based formulation containing morin. CONCLUSIONS: Morin showed an anti-inflammatory and antioxidant effect as well as antimicrobial properties against periodontal pathogens. In addition, polymer-based formulation enhanced these effects.